Cover Feature: Large Electro‐Optic Kerr Effect in Ionic Liquid Crystals: Connecting Features of Liquid Crystals and Polyelectrolytes (ChemPhysChem 18/2018). Issue 18 (31st August 2018) - Schlick, M. Christian; Kapernaum, Nadia; Neidhardt, Manuel M.; Wöhrle, Tobias; Stöckl, Yannick; Laschat, Sabine; Giesselmann, Frank
Abstract : The Cover Feature shows an ionic liquid crystal (ILC, see molecular model) on interdigitating platinum‐electrodes (background) which were used to measure the huge electro‐optic Kerr effect in the isotropic phase of this ILC. The diagram in the lower left corner depicts the field‐induced birefringence plotted according to Kerr's law. More information can be found in the Article by M. C. Schlick et al. onpage 2305 in Issue 18, 2018 (DOI:10.1002/cphc.201800347 ).